2022
DOI: 10.3390/vaccines10050783
|View full text |Cite
|
Sign up to set email alerts
|

Probable Vogt–Koyanagi–Harada Disease after COVID-19 Vaccination: Case Report and Literature Review

Abstract: COVID-19 vaccination is considered the most effective and promising approach for the elimination of the SARS-CoV-2 pandemic globally. Although the vaccine has been proven to be safe, as evidenced by the promotion of mass vaccination, new side effects, including several ocular complications that were not described during the experimental stage, are now emerging. In the present study, we report a 33-year-old Chinese man who developed probable Vogt–Koyanagi–Harada (VKH) disease only one day after his first dose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…A total of 65 studies were both qualitatively and quantitatively analyzed ( Table 1 ) [ 1 , 5 , 7 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ,…”
Section: Resultsmentioning
confidence: 99%
“…A total of 65 studies were both qualitatively and quantitatively analyzed ( Table 1 ) [ 1 , 5 , 7 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ,…”
Section: Resultsmentioning
confidence: 99%
“…Saraceno et al first described a patient diagnosed with complete VKH syndrome 4 days after receiving COVID-19 immunization with the Oxford-AstraZeneca Chimpanzee Adenovirus Vectored Vaccine ChAdOx1 nCoV-19 (AZD1222) [13]. In a previous study, we also reported that a 33-year-old Chinese man developed probable VKH disease only one day after his first dose of an inactivated COVID-19 vaccine and summarized the clinical characteristics of VKH disease in temporal association with COVID-19 vaccination [4]. Different possibilities regarding the causality of VKH and vaccination have been raised, including adjuvants [13], the antigen mimicry [8], and structural surface glycoprotein antigen [12].…”
Section: Discussionmentioning
confidence: 96%
“…VKH disease closely related to vaccines against SARS-CoV-2 is a quite rare event, although it has been recognized [3,4,8,9,[12][13][14][15]. Papasavvas et al reported the reactivation of well-controlled VKH disease for more than 6 years following an anti-SARS-CoV-2 vaccination [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations